The Influence of Gender on Speaking Competency - Utama, Gede Yasa (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This article is aimed at revealing an idea that gender can influence someone’s speaking competency. Speaking competency is an ability in speaking that includes the skills, knowledge, and attitudes of someone in performing speaking. Gender is psychosocial status associated with something that is done or performed by a person, which is reflected in the ways shown in the conduct or display something in the community in accordance with the and the underlying culture. This article used library research method, since the subject is an idea which is needed to be extended. Having gathered the data from some researches about the influence of gender on speaking competency, it is found that males, depending of his cultural background, tend to be more active than females toward the oral proficiency. However, regarding at speaking competency such us pronunciation and vocabulary, females are better than males.